Randomised trial of population‐based BRCA testing in Ashkenazi Jews: long‐term outcomes. (10th September 2019) - Manchanda, R; Burnell, M; Gaba, F; Desai, R; Wardle, J; Gessler, S; Side, L; Sanderson, S; Loggenberg, K; Brady, AF; Dorkins, H; Wallis, Y; et al.
Abstract : Objective: Unselected population‐based BRCA testing provides the opportunity to apply genomics on a population‐scale to maximise primary prevention for breast‐and‐ovarian cancer. We compare long‐term outcomes of population‐based and family‐history (FH)/clinical‐criteria‐based BRCA testing on psychological health and quality of life. Design: Randomised controlled trial (RCT) (ISRCTN73338115) GCaPPS, with two‐arms: (i) population‐screening (PS); (ii) FH/clinical‐criteria‐based testing. Setting: North London Ashkenazi‐Jewish (AJ) population. Population/Sample: AJ women/men. Methods: Population‐based RCT (1:1). Participants were recruited through self‐referral, following pre‐test genetic counselling from the North London AJ population. Inclusion criteria : AJ women/men >18 years old; exclusion‐criteria: prior BRCA testing or first‐degree relatives of BRCA ‐carriers. Interventions : Genetic testing for three Jewish BRCA founder‐mutations: 185delAG (c.68_69delAG), 5382insC (c.5266dupC) and 6174delT (c.5946delT), for (i) all participants in PS arm; (ii) those fulfilling FH/clinical criteria in FH arm. Linear mixed models and appropriate contrast tests were used to analyse the impact of BRCA testing on psychological and quality‐of‐life outcomes over 3 years. Main outcome measures: Validated questionnaires (HADS/MICRA/HAI/SF12) used to analyse psychological wellbeing/quality‐of‐life outcomes at baseline/1‐year/2‐year/3‐year follow up. Results: In all, 1034 individuals (691 women, 343 men) were randomised to PS ( n  = 530) or FH ( n  = 504) arms. There was a statistically significant decrease in anxiety ( P  = 0.046) and total anxiety‐&‐depression scores ( P  = 0.0.012) in the PS arm compared with the FH arm over 3 years. No significant difference was observed between the FH and PS arms for depression, health‐anxiety, distress, uncertainty, quality‐of‐life or experience scores associated with BRCA testing. Contrast tests showed a decrease in anxiety ( P  = 0.018), health‐anxiety ( P  < 0.0005) and quality‐of‐life ( P  = 0.004) scores in both PS and FH groups over time. Eighteen of 30 (60%) BRCA carriers identified did not fulfil clinical criteria for BRCA testing. Total BRCA prevalence was 2.9% (95% CI 1.97–4.12%), BRCA1 prevalence was 1.55% (95% CI 0.89–2.5%) and BRCA2 prevalence was 1.35% (95% CI 0.74–2.26%). Conclusion: Population‐based AJ BRCA testing does not adversely affect long‐term psychological wellbeing or quality‐of‐life, decreases anxiety and could identify up to 150% additional BRCA carriers. Tweetable abstract: Population BRCA testing in Ashkenazi Jews reduces anxiety and does not adversely affect psychological health or quality of life. Tweetable abstract: Population BRCA testing in Ashkenazi Jews reduces anxiety and does not adversely affect psychological health or quality of life. This paper includes Author Insights, a video abstract available at https://vimeo.com/rcog/authorinsights15905